Bodily Discipline and Spiritual Bodily Discipline and Spiritual Genealogy: Analyzing Bunyai Zakiyah's Asceticism Through a Foucaultian, Phenomenological, and Sufism Lens - Dewi Masita; Ila Rokhani Ila Rokhani (Journal of Social and Humanities, 2025)
This study examines the asceticism of Bunyai Zakiyah, a spiritual leader at Pesantren Al-Yasini in Pasuruan Regency, as a profound religious practice that shapes communal identity. Integrating Foucauldian analysis of bodily discipline and power-knowledge, phenomenology through Interpretative Phenomenological Analysis, and tasawuf perspectives on spiritual genealogy, the research explores how asceticism functions as a holistic process of subject formation. The study aims to describe forms of bodily discipline through a Foucauldian lens, uncover the meaning of lived experience phenomenologically, and reconstruct spiritual genealogy within a Sufi framework. A qualitative phenomenological ethnography was employed, drawing on 20 in-depth interviews with Bunyai Zakiyah, her children, and alumni, six months of participant observation, and document analysis including sanad of the tarekat. Findings show that practices such as 40 days of fasting and silent dhikr constitute strict bodily discipline under communal supervision, resembling a spiritual panopticon. Lived experiences of physical endurance are interpreted as transformative processes that generate transcendence and social connectedness. Furthermore, spiritual genealogy rooted in the Naqsyabandiyah-Khalidiyah sanad and piety narratives establishes enduring spiritual authority and cohesive social relations. The interdisciplinary synthesis reveals asceticism as a form of “spiritual discipline” that transforms regulated bodies into liberated spiritual subjects. The study contributes theoretically to interdisciplinary Islamic studies, methodologically through the application of IPA in religious research, and practically to spiritual education and community development within Indonesian pesantren contexts.